Comparison of oxygen reduction reaction on Pt/C, Pt-Sn/C, Pt-Ni/C, and Pt-Sn-Ni/C catalysts prepared by Bönnemann method: A rotating ring disk electrode study. (1st January 2015) - Beyhan, Seden; Şahin, Nihat Ege; Pronier, Stéphane; Léger, Jean-Michel; Kadırgan, Figen
Graphical abstract: Highlights: Enhancement in the ORR activity by the presence of either Sn or Ni in Pt/C. Higher ORR performance of Pt-Sn/C compared to Pt-Ni/C and Pt-Sn-Ni/C. Both the adsorption of oxygen and water on Pt-Sn/C plays a crucial role for ORR. Abstract: The kinetics of oxygen reduction reaction (ORR) on carbon supported Pt, Pt-Sn, Pt-Ni, and Pt-Sn-Ni catalysts, prepared by Bönnemann method, is investigated by using rotating ring disk electrode (RRDE) measurements in 0.1 M HClO4 solution. Physical characterization of the catalysts is performed by X-ray diffraction (XRD), high resolution transmission electron microscopy (HR-TEM), energy dispersive X-ray (EDX) analysis and X-ray photoelectron spectroscopy (XPS) techniques. The cyclic voltammetry (CV) measurement has been used to estimate the electrochemical active surface (EAS) area of the catalyst. The enhancement in the ORR activity of the Pt/C observed in the presence of either Sn or Ni, leading to more than 99% of water formation. However, Pt-Sn/C catalyst shows a higher ORR performance as compared to the Pt-Ni/C and Pt-Sn-Ni/C catalysts. This can be explained by the presence of optimal amount of Sn oxides as an unalloyed state in Pt-Sn/C, which plays a beneficial role for both adsorption oxygen and water. On the other hand, it is found that the alloying Pt with Ni seems to be less favourable for the ORR performance.